(untitled) (AYUSHDHARA, 2023)
On 2nd of March 2023, a massive fire incident happened in Brahmapuram dump yard which resulted in dense smoke enveloping Kochi and nearby premises, suffocating the inhabitants thereafter; acute manifestations of inhaling noxious air were present and none the less are the long-time health hazards that Kochi must face in coming years. Destruction of a community with similarity in disease manifestation, especially within a geographical area, because of Adharma, Pragnjaparadha can be related with Janapadodhwamsa, for which this fire incident can be an epitome. Ayurveda, a science that believe in prevention of a disease, can help in preventing the long-time health hazards that probably can happen after this dump yard fire incident. Aim: To review and analyze the Brahmapuram fire incident with respect to Janapadodhwamsa and to highlight the Ayurvedic preventive measures that can be adopted against the probable long time health hazards. Materials and Methods: Addressing the long-time health impacts that the fire incident could produce with respect to Janapadodhwamsa, helps in understanding the same as an environmental disaster impacting health of inhabitants. The approach consisted of thorough searching of several resources which includes Ayurvedic treatises, books, dissertations, conference proceedings, web based scientific databases, e-newspapers and recent updates from all available sources. Conclusion: Since the incident was massive of its kind, but had frequently occurred in a smaller dimensions even before, emphasised the need of a review of why the incident occurred, analysing the health impacts it could produce. Thus, this article emphasises the role of Ayurveda in prevention of long time health hazards that it can produce in the residents of the city.